Development, Characterization, Stability and Bioaccessibility Improvement of 7,8-Dihydroxyflavone Loaded Zein/Sophorolipid/Polysaccharide Ternary Nanoparticles: Comparison of Sodium Alginate and Sodium Carboxymethyl Cellulose - Yufeng Chen (MDPI AG, 2021)
In this study, two polysaccharides [sodium alginate (ALG) and sodium carboxymethyl cellulose (CMC)] were selected to establish zein/sophorolipid/ALG (ALG/S/Z) and zein/sophorolipid/ALG (CMC/S/Z) nanoparticles to encapsulate 7,8-dihydroxyflavone (7,8-DHF), respectively. The results showed that polysaccharide types significantly affected performance of ternary nanoparticles, including CMC/S/Z possessed lower polydispersity index, particle size and turbidity, but higher zeta potential, encapsulation efficiency and loading capacity compared to ALG/S/Z. Compared to zein/sophorolipid nanoparticles (S/Z), both ALG/S/Z and CMC/S/Z had better stability against low pH (pH 3~4) and high ionic strengths (150~200 mM NaCl). Hydrophobic effects, electrostatic interactions and hydrogen bonding were confirmed in ternary nanoparticles fabrication via Fourier-transform infrared spectroscopy. Circular dichroism revealed that CMC and ALG had no evident impact on secondary structure of zein in S/Z, but changed surface morphology of S/Z as observed by scanning electron microscope. Encapsulated 7,8-DHF exhibited an amorphous state in ternary nanoparticles as detected by X-ray diffraction and differential scanning calorimetry. Furthermore, compared to S/Z, ALG/S/Z, and CMC/S/Z remarkably improved the storage stability and bioaccessibility of 7,8-DHF. CMC/S/Z possessed a greater storage stability for 7,8-DHF, however, ALG/S/Z exhibited a better in vitro bioaccessibility of 7,8-DHF. This research provides a theoretical reference for zein-based delivery system application.